2019
DOI: 10.1007/s12046-019-1185-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization of process parameter in EDM using low-frequency vibration of workpiece assigned for SKD61

Abstract: Integrated vibration in electrical discharge machining (EDM) plays a key role in achieving high efficiency. High levels of variables can be employed in this approach due to integration. However, simultaneous optimization of the EDM parameters to achieve multi-objectives is still very complex and challenging. Studies on integrated vibration are still in a preliminary stage. This report addresses multi-objective optimization in EDM for SKD61 die steel using low-frequency vibration. MOORA (Multi-objective optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Its unit is defined as mm 3 /min. It is an important parameter for determining the productivity of EDM [20]. The weight of the work piece before and after the machining was measured using a microweight balance (Citizen System-CX 165, London, UK) of a least count of 0.001 g. This variance was then divided by the density of the work piece material and machining time to evaluate the MRR using Equation (1):…”
Section: Design Of Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its unit is defined as mm 3 /min. It is an important parameter for determining the productivity of EDM [20]. The weight of the work piece before and after the machining was measured using a microweight balance (Citizen System-CX 165, London, UK) of a least count of 0.001 g. This variance was then divided by the density of the work piece material and machining time to evaluate the MRR using Equation (1):…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…It also has a unit of mm 3 /min. It is an important parameter that determines the processing cost and accuracy of the process [20]. The tool was weighed before and after the machining on the microweight balance and the weight difference was used to calculate the TWR.…”
Section: Tool Wear Ratementioning
confidence: 99%
“…Based on GRA technique, Tharian et al [20] performed multi-objective optimization of MRR and SR during EDM operation of Al7075 alloy. Huu et al [21] proposed the application of multi-objective optimization based on ratio analysis (MOORA) method for having better values of MRR, SR and TWR during EDM operation of SKD61 die steel with low-frequency vibration. Analytic hierarchy process (AHP) was utilized to estimate relative weights of the considered responses.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Based on the GRA technique, Tharian et al [ 21 ] implemented a multi-objective optimization of MRR and SR during an EDM operation of Al7075 alloy. Huu et al [ 22 ] suggested, as a solution, the multi-objective optimization based on ratio analysis (MOORA) methodology for having the best results of MRR, SR and TWR throughout the EDM operation of SKD61 die steel with low-frequency vibration. Analytic hierarchy process (AHP) was utilized to estimate relative weights of the considered responses.…”
Section: Introductionmentioning
confidence: 99%